2008
DOI: 10.1117/1.2907699
|View full text |Cite
|
Sign up to set email alerts
|

Differential permeability rate and percent clearing of glucose in different regions in rabbit sclera

Abstract: Imaging of biological tissues with optical coherence tomography (OCT) poses a great interest for its capability to noninvasively outline subsurface microstructures within tissues. However, a major limitation for many optical imaging techniques is inadequate depth penetration of light in turbid media, which is bounded to just a few millimeters. There have been several attempts to improve light penetration depth in biological tissues, including application of different tissue optical clearing methods. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…Optical clearing of tissues induces tissue dehydration and refractive index matching by agent inclusion in the interstitial space of the tissue [3]. By placing an OCA in the interstitial space of the tissue and reducing the water content, the refractive index difference between the scatterers and the interstitial presented with results for the diffusion time for some OCAs such as dimethyl sulfoxide [17], glucose [18][19][20], mannitol [18], sucrose [21], glycerol [22], lactose and fructose [21] in different biological tissues and phantoms. A study that was recently published provided results for glucose diffusion permeability in normal and cancerous oesophageal tissues [23].…”
Section: Introductionmentioning
confidence: 99%
“…Optical clearing of tissues induces tissue dehydration and refractive index matching by agent inclusion in the interstitial space of the tissue [3]. By placing an OCA in the interstitial space of the tissue and reducing the water content, the refractive index difference between the scatterers and the interstitial presented with results for the diffusion time for some OCAs such as dimethyl sulfoxide [17], glucose [18][19][20], mannitol [18], sucrose [21], glycerol [22], lactose and fructose [21] in different biological tissues and phantoms. A study that was recently published provided results for glucose diffusion permeability in normal and cancerous oesophageal tissues [23].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are overviewed in Refs. 3, 4, 11-17 and recent ones present optical clearing of tissues such as skin, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sclera, [33][34][35] and skeletal muscle. [36][37][38][39][40][41] We have found that only in two papers optical clearing of heart tissues were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore difficult to quantitatively compare directly the MIP derived permeability (in units of area) and the OCT measured hydraulic conductivity (in units of speed). In OCT applications to biological tissues, fluid flow rate is often quoted as a permeability coefficient [20,21], which is not the same as the intrinsic permeability described above.…”
Section: Resultsmentioning
confidence: 99%
“…OCT produces noninvasive and nondestructive depth resolved quantification of hydraulic conductivity in sandstones and other porous materials to determine vulnerability of the material to weathering. This is analogous to OCT monitoring of the permeability coefficient of aqueous glucose solution in biological tissues [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation